Genre system of traditional music in context life cycle (Eurasian Journal of Philology Science and Education, 2018)
In this article an attempt was made to reveal the integral nature of the existing genre variety, to determine the composition, evolution and interaction of the genres of the song and instrumental creativityof Kazakhs. Experiencing various influences, being formed on the basis of chronical traditions, traditionalKazakh music, conditioned by historical development, forms a kind of integrity, embodied in the genresystem. The genre system of Kazakh musical and poetic creativity was formed on the basis of the life as areflection of its content, consisting of songs of childhood, youth, maturity, old age. Musical and linguisticbase of folklore and professional art is given due to which the highest level and democracy of nomadicculture, the highest spiritual and artistic values of which were the property of the whole society was possible. Uniting space, natural and socio – cultural phenomena in the life of the traditional Kazakh society,mushel demonstrates the original inseparability, inseparable connection of macro-and microcosm